2020
DOI: 10.1007/s00586-020-06626-x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of topical use of tranexamic acid in reducing blood loss on early operation for thoracolumbar burst fracture: a randomized double-blinded controlled study

Abstract: Purpose To investigate the safety and efficacy of topical use of tranexamic acid (TXA) on early operation for thoracolumbar burst fracture (TBF). Methods Patients with acute TBF requiring early decompression were prospectively collected. The enrolled patients were randomly assigned to TXA and control group, in which wound surface was soaked with TXA or the same volume of normal saline for 5 min after wound incision, respectively. The total blood loss (TBL), intraoperative blood loss (IBL), postoperative blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 27 publications
1
25
0
Order By: Relevance
“…This finding emphasizes the key role of topical TXA in the reduction of blood loss during surgery; this can result in better visualization, less operation time, and a decrease in surgical complications. Our results are in agreement with the recent study, which demonstrated that topical TXA can decrease IBL in the surgical treatment of thoracic burst fracture [29].…”
Section: Discussionsupporting
confidence: 94%
“…This finding emphasizes the key role of topical TXA in the reduction of blood loss during surgery; this can result in better visualization, less operation time, and a decrease in surgical complications. Our results are in agreement with the recent study, which demonstrated that topical TXA can decrease IBL in the surgical treatment of thoracic burst fracture [29].…”
Section: Discussionsupporting
confidence: 94%
“…24 Of these, 7 were prospective randomized trials, 1 was a retrospective cohort study, and 1 prospective observational study. [24][25][26][27][28][29][30][31][32] Combined, the total participant strength was 828 patients. The PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) flow diagram is shown in Figure 1.…”
Section: Search Resultsmentioning
confidence: 99%
“…Total Blood Loss TBL was reported in 3 studies with a total of 4 groups. 28,29,31 A random effects model was used due to significant heterogeneity (I 2 = 96%, P < 0.00001). A significant effect was noted in terms of TBL (standard mean difference [SMD] = −2.54 [95% CI, −3.72, −1.37], P = 0.0001) (Figure 1).…”
Section: Outcomes For Meta-analysismentioning
confidence: 99%
See 2 more Smart Citations